Global Transformations and the MENA: A Comparative Political Economy Analysis - Unay, Sadik (SETA FOUNDATION, 2011)
The regional geographical entity known as the Middle East and North Africa (MENA) has been at the epicenter of global power struggles over the course of the last centuries with an ever-increasing intensity. While the region has been a popular subject in the literature of political science and international relations due to the sheer volume of conflicts raging within the parameters of its borders, writings on international/ comparative political economy focused on alternate regions such as East Asia characterized by a sustainable economic growth potential. This study aims to make a critical contribution to the political economy literature by conducting a theoretically and historically informed analysis on the transformation dynamics in the MENA region. To this end, the multi-faceted legacy of colonialism; the role of oil as a strategic resource; structural changes in the world economy; and divergent politico-economic reform trajectories in the wake of economic globalization will be evaluated.
Keywords: Government & Law